2009
DOI: 10.2463/mrms.8.187
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Presumed Hemorrhage in the Ampullar Endolymph of the Semicircular Canal: A Case Report

Abstract: We examined a 61-year-old woman with sudden left-side hearing loss accompanied by severe vertigo. High signal in the ampullar endolymph of the left semicircular canal on magnetic resonance (MR) ‰uid attenuated inversion recovery (3D-FLAIR) images suggested labyrinthine hemorrhage. The patient had been treated for chronic heart failure and prescribed 100 mg/day of acetylsalicylic acid (aspirin) for its antiplatelet eŠect. The 3D-FLAIR images demonstrated a small amount of focal hemorrhage in the labyrinthine ‰u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Findings obtained using three-dimensional fluidattenuated inversion recovery magnetic resonance imaging (3D-FLAIR MRI) provided supporting evidence that a pathologic alteration occurs within the inner ear fluid in SSNHL patients with or without vertigo, in which high pre-contrast signals were observed within the inner ear on 3D-FLAIR (22,23). Pre-contrast high signals on 3D-FLAIR may reflect a minor hemorrhage or an increased inner ear concentration of proteins that were extravasated through blood vessels with increased permeability or originated from damaged cells in the inner ear (24).…”
Section: Discussionmentioning
confidence: 91%
“…Findings obtained using three-dimensional fluidattenuated inversion recovery magnetic resonance imaging (3D-FLAIR MRI) provided supporting evidence that a pathologic alteration occurs within the inner ear fluid in SSNHL patients with or without vertigo, in which high pre-contrast signals were observed within the inner ear on 3D-FLAIR (22,23). Pre-contrast high signals on 3D-FLAIR may reflect a minor hemorrhage or an increased inner ear concentration of proteins that were extravasated through blood vessels with increased permeability or originated from damaged cells in the inner ear (24).…”
Section: Discussionmentioning
confidence: 91%
“…[21][22][23][24][25][26][27][28][29][30] A FLAIR image allows the detection of subtle subarachnoid hemorrhage in the CSF space, 9 signal increases in CSF after the inhalation of oxygen, 31 and subtle compositional changes of the labyrinthine fluid (Figs. 6 and 7), 26,27,30,[32][33][34] which can be difficult to recognize on T 1 -weighted images. Heavily T 2 -weighted 3D-FLAIR has been reported to be much more sensitive than regularcontrast 3D-FLAIR.…”
Section: T 2 -Selective Inversion Recoverymentioning
confidence: 99%
“…Recently, it was reported that the condition of the light cupula is responsible for the positional vertigo in some patients with sudden sensorineural hearing loss (SSNHL) [2]. Findings obtained using 3-dimensional fluid-attenuated inversion recovery magnetic resonance imaging (3D-FLAIR MRI) in patients with SSNHL with vertigo indicated a minor hemorrhage or an increased concentration of proteins in the inner ear presumably due to a disruption of the blood-labyrinth barrier [10,11]. The blood-labyrinth barrier has been reported to be disrupted by various causes such as microcirculatory compromise, infection, and acoustic trauma [12][13][14].…”
Section: Evaluation Of Hypotheses and Discussionmentioning
confidence: 98%